2019
DOI: 10.1523/eneuro.0503-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 1 Regulates Network Ensembles and Dendritic Spine Development in Cortical Neurons

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 86 publications
(108 reference statements)
6
42
0
Order By: Relevance
“…Consistent with our observations in spine density, it was recently shown that Panx1 negatively regulates cortical dendritic spine development and network connectivity (Sanchez-Arias et al, 2019); however, the underlying mechanism has not yet been resolved. Which of the synaptic mechanisms governing the induction of synaptic plasticity could be impacted by an exacerbated Panx1 activity?…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our observations in spine density, it was recently shown that Panx1 negatively regulates cortical dendritic spine development and network connectivity (Sanchez-Arias et al, 2019); however, the underlying mechanism has not yet been resolved. Which of the synaptic mechanisms governing the induction of synaptic plasticity could be impacted by an exacerbated Panx1 activity?…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it has been reported that Aβ induces aberrant actin polymerization, affecting actin dynamics through a mechanism involving p38MAPK activity (Song et al, 2002). Interestingly, Panx1 channels interact with actin filaments (Bhalla-Gehi et al, 2010) and actin-binding proteins (Wicki-Stordeur and Swayne, 2013;Boyce et al, 2014) and have been shown to participate in the modulation of actin-dependent changes in neuronal morphology (Wicki-Stordeur and Swayne, 2013;Sanchez-Arias et al, 2019). This latter, added to our observations that PBN reverses a deficient dendritic branching and spine density in the Tg hippocampal tissue (Figure 4), strongly suggests that synaptic defects in the AD context rely on Panx1-induced signaling producing actindependent structural defects.…”
Section: Discussionmentioning
confidence: 99%
“…Pannexin 1 (PANX1) is a four transmembrane domain protein that forms channels permeable to ions and metabolites with various activation mechanisms and diverse (patho)physiological implications (for review Boyce et al, 2018;Chiu et al, 2018). PANX1 is broadly and highly expressed in the brain during early postnatal development (Ray et al, 2005;Vogt et al, 2005) and localized and enriched in synaptic compartments (Zoidl et al, 2007;Sanchez-Arias et al, 2019). Pharmacological and genetic disruption of PANX1 results in enhanced hippocampal LTP induction while precluding that of LTD (Prochnow et al, 2012;Ardiles et al, 2014;Gajardo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological and genetic disruption of PANX1 results in enhanced hippocampal LTP induction while precluding that of LTD (Prochnow et al, 2012;Ardiles et al, 2014;Gajardo et al, 2018). Given that PANX1interacting cytoskeletal regulators, collapsin response mediator protein 2 (CRMP2) and actinrelated protein 2/3 complex (ARP2/3), are known to control dendritic spine formation (Wicki-Stordeur and Swayne, 2013;Spence et al, 2016;Zhang et al, 2016;Xu et al, 2018), it was perhaps not surprising that Sanchez-Arias et al (2019) recently showed that Panx1 deletion led to the formation of larger cortical neuron network ensembles and that this was due, in part, to increased cortical neuron dendritic spine density.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, we found that Panx1 inhibits neurite development in Neuro2a (N2a) and neural precursor cells (Wicki-Stordeur and Swayne, 2013). Similarly, cortical neurons from Panx1 knockout mice demonstrated an increased density of dendritic spines, as well as larger groups of co-activated neurons, also known as network ensembles (Sanchez-Arias et al, 2019). This regulation of neurites and dendritic spines connects nicely with our earlier discovery of Panx1 proteinprotein interactions (PPIs) with dendritic spine regulating proteins, such as the actin-related protein (Arp) 2/3 complex components (Wicki-Stordeur and Swayne, 2013), and the microtubule-interacting protein collapsin-response mediator protein 2 (Crmp2) (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 84%